Associations Between Antioxidant Vitamin Status, Dietary Intake, and Retinol-binding Protein 4 Levels in Prepubertal Obese Children After 3-month Weight Loss Therapy - Joanna Gajewska; Jadwiga Ambroszkiewicz; Katarzyna Szamotulska; Witold Klemarczyk; Halina Weker; Magdalena Chełchowska (JCRPE, 2021)

(untitled)
Objective:Adiposity is associated with increased oxidative stress, leading to changed fat-soluble vitamin concentrations. The aim of this study was to determine whether weight loss alters fat-soluble vitamin status and whether these alterations are associated with dietary intake, anthropometric parameters and adipokines in obese children.Methods:Vitamin A and E concentrations were measured using high-pressure liquid chromatography in 60 obese children before and after weight loss therapy. Retinol-binding protein 4 (RBP4), leptin, soluble leptin receptor (sOB-R), and high molecular weight adiponectin concentrations were determined by immunoenzymatic assays.Results:The intake of vitamin E was lower in obese children with weight loss after therapy (p=0.038). In this group, an increase was found in the vitamin A/lipids (p=0.022) and the vitamin E/lipids (p=0.008) ratios but due to the reduction in triglyceride levels. In the obese group, changes in vitamin E level were positively correlated with changes in dietary vitamin E (p=0.017) and the leptin/sOB-R ratio (p=0.046). Changes in vitamin A level were positively correlated with changes in dietary vitamin A (p=0.001) and RBP4 concentration (p=0.023). Associations between changes in RBP4 level with the changes in body mass index (BMI) (p=0.011) and total cholesterol concentration (p=0.023) but not with changes in vitamin A concentration were found in the obese after therapy.Conclusion:An increased risk of vitamin E deficiency may occur in children losing weight during lifestyle intervention. Changes in BMI value may influence changes in RBP4 concentrations and consequently the vitamin A status in obese children after therapy.